Estratégias de suplementação de caprinos em pastagem de Tifton 85 - Ruoso, Angela (2013)
Goats and kids production on high quality pasture, especially involving supplementation use, demand more research information to indicate best supplementation procedure to be used. In this sense, this trial aimed to evaluate herbage production and structural composition of the pasture and goats and their kids performance under supplementation strategies (with and without supplement) on black oat plus Tifton 85 pasture, in continuous stocking to keep sward canopy height from 15 to 20 cm. The experiment was carried out from October 2011 to April 2012 (198 days). Boer goats with gemelar birth (72 animals) were used. Completely randomized blocks in 2x2 factorial design was used with three replications. First factor was presence and absence of goats supplementation and the second was presence and absence kids supplementation. Supplemented goats were fed at 1% of body weight of supplement. Kids were fed ad libitum, from birth to slaughter. Creep feeding was used until weaning. Herbage production, crude protein content, leaf and stem mass, and leaf/stem ratio were not affected by supplementation strategies. Dead material mass was higher in kids supplemented treatments. Herbage allowance was 7.11 kg of DM 100-1 kg body weight when kids were supplemented and 11.4 kg of DM 100-1 kg body weight when kids were kept only grazing. It was observed substitutive effect of forage by supplement intake, because supplemented kids had lesser grazing time than no supplemented ones. Use of supplement for the goats did not promoted higher average weight daily gain and body score condition as expected. It was verified body weight loss at the beginning of lactation. Supplementation use for the goats did not affect their kids performance, which was similar of the non-supplemented goat kids performance. Supplementation for kids increased animal performance and animal production per ha, and lesser parasite contamination driving to higher carcass yield and body score condition than non-supplemented kids. Lactating goats supplementation on Tifton 85 pasture is not recommended. Supplement may be used for breast-feeding kids by creep feeding.